Development of Statistical Literacy-based Mathematics Module for Junior High School Students in the Context of MSMEs’ Empowerment - Subekti, Fitrianto Eko; Gunawan, Gunawan; Ong, Eng Tek; Akhsani, Lukmanul; Zuhrotunnisa, Zuhrotunnisa (FKIP Universitas Lampung, 2025)
Statistical Literacy is needed by students in understanding information and presenting data in various forms of representation. This study aims to develop a mathematics module based on statistical literacy for junior high school students in the context of empowering Micro, Small, and Medium Enterprises (MSMEs) that is valid, practical, and effective. The research method uses a development research design with ASSURE stages. Twenty students of class VIII A were used as research samples, considering the ease and accessibility in conducting the research. Validity data were obtained through a validation questionnaire assessed by competent experts in their fields. Practicality data were obtained through a student response questionnaire. Effectiveness data were obtained based on the results of the statistical literacy pre-test and post-test. While observation data were used as supporting data to describe the module trial activities in learning. Quantitative data analysis used average values to analyze the results of the validation questionnaire and student responses, as well as the Wilcoxon test to determine the effectiveness of the developed module in learning. The validation results show that the developed module meets the validity criteria and receives positive responses from students and teachers. In addition, the Wilcoxon test results indicate the influence of module use in learning, that supported by the N-Gain test results of 0.59, indicating that the developed learning module is quite effective in improving students' statistical literacy. Although the development results are quite effective, students need to be accustomed to dealing with problems that contain the surrounding context, increase assignments, and integrate strategies, media, and learning models that focus on developing statistical literacy. Thus, the developed module has met the criteria of validity, practicality, and effectiveness. However, the results of the statistical literacy test evaluation indicate limitations in students' abilities to interpret and draw conclusions. This research provides an important contribution in developing relevant, innovative teaching materials, while highlighting crucial aspects for future learning, especially focusing on statistical literacy and contextual-based learning. Keywords: statistical literacy, MSMEs empowerment, statistical module.